Адаптивний нагрів виробничого приміщення - Кривко, М. Ю. (My University, 2020)
In the given work The thermal model of the room, developed using modern information technologies, is used that is used to save energy when heating it. The model takes into account both the change in ambient temperature and the temperature in the adjacent room, as well as the parameters of the building. An algorithm for controlling the temperature in a room using the developed modelis proposed.
Keywords: системи вентиляції; адаптивний нагрів; клімат